1959
DOI: 10.1038/icb.1959.13
|View full text |Cite
|
Sign up to set email alerts
|

A VIRUS OF THE ENCEPHALOMYOCARDITIS GROUP FROM A WATER‐RAT, HYDROMYS CHRYSOGASTER, IN NORTH QUEENSLAND

Abstract: A virus, referred to as the Innisfail strain, was isolated by mouse inoculation horn a naturally Infected water-rat, Hydromys chrysogaster, captured in north Queensland, Australia. It was shown to be indistinguishable from the EMC vims of Helwig and Schmidt by cross-neutralization and cross-complement fixation tests, and was considered to belong to the EMC group of viruses.Mice and guinea-pigs were highly susceptible. Rats showed signs of paralysis, but usually survived. Rabbits and three-day-old chickens were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

1965
1965
1985
1985

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 2 publications
0
8
0
3
Order By: Relevance
“…Until recently it has been assumed that rodents, especially rats, are the natural reservoir of EMC virus due to the high prevalence of EMC antibody in this species [Andrewes and Pereira, 1978;Melnick et al, 1974;Warren, 19651. This ha5 been based on the observation that the virus has frequently been associated with wild rodents, and has been recovered on occasion from the tissues and feces of rats following parenteral administration [Andrewes and Pereira, 1978;Kilham et al, 1956;Pope, 1959;Roca Garcia and SanMartin-Barberi, 1957;Vanella et al, 1956;Warren, 1965;Warren et al, 19491. However, recent laboratory studies have shown that although oral administration of viruses to rats results in infection as indicated by subsequent antibody formation, shedding of virus and infection of cage mates is rare [Tesh and Wallace, 19781. In addition, virus isolation from rat tissues and clinical illness in this setting are uncommon.…”
Section: Nd"mentioning
confidence: 99%
“…Until recently it has been assumed that rodents, especially rats, are the natural reservoir of EMC virus due to the high prevalence of EMC antibody in this species [Andrewes and Pereira, 1978;Melnick et al, 1974;Warren, 19651. This ha5 been based on the observation that the virus has frequently been associated with wild rodents, and has been recovered on occasion from the tissues and feces of rats following parenteral administration [Andrewes and Pereira, 1978;Kilham et al, 1956;Pope, 1959;Roca Garcia and SanMartin-Barberi, 1957;Vanella et al, 1956;Warren, 1965;Warren et al, 19491. However, recent laboratory studies have shown that although oral administration of viruses to rats results in infection as indicated by subsequent antibody formation, shedding of virus and infection of cage mates is rare [Tesh and Wallace, 19781. In addition, virus isolation from rat tissues and clinical illness in this setting are uncommon.…”
Section: Nd"mentioning
confidence: 99%
“…Heart lesions, but no deaths, were induced in 5 pigs fed high doses ( > lo9 mouse LDBo) of 5th mouse passage virus, and fatal disease in 1 pig fed several 1st mouse passage carcasses. Watt and Spradbrow (1974) have reported infection and fatal disease in 2 pigs after intracerebral inoculation of a strain recovered from a water rat in Queensland by Pope (1959). The same material given intraperitoneally failed to infect 1 pig.…”
Section: Introductionmentioning
confidence: 99%
“…Encephalomyocarditis (EMC) virus has been recovered from many animal species, mainly rodents, pigs and primates, and is believed to be maintained in nature by rodents (Warren 1965). In Australia, the first recovery of EMC virus was from a water rat captured in the Innisfail district of Queensland (Pope 1959). Serological surveys, performed mainly on Queensland animals, have shown antibodies to EMC virus to be present in a small percentage of rodents and horses (Pope and Scott 1960), pigs (Spradbrow 1968) and cattle (Spradbrow and Chung 1970). EMC virus was first recorded as a cause of pig mortality by Murnane et al (1960) in Panama.…”
Section: Introductionmentioning
confidence: 99%